Technical Progress and Structural Change in the Process of Economic Development - Massimo Ricottilli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1990)
Economic development is, in essence, structural change. The latter if it is to be of a progressive kind requires, in turn, progress in modes of production.
Keywords: 330